In-use contamination of propofol: a clinical study - Bach, Alfons; Motsch, Johann; Schmidt, Heinfried; Böttiger, Bernd W.; Böhrer, Hubert; Martin, Eike; Sonntag, Hans-Günther (European journal of anaesthesiology, 1997)
Reports about post-operative infections associated with the use of propofol prompted us to investigate the in-use contamination of lipid-formulated intravenous (i.v.) anaesthetics used for general anaesthesia or for sedation of intensive care patients in this department. The level and incidence of extrinsic contamination of propofol («Diprivan») and of another intravenous anaesthetic, etomidate, formulated in lipid solution («Etomidat-lipuro») was found to be low during two study periods. However, the need to observe strict aseptic precautions in handling these intravenous drugs must be emphasized..
Elektronische Reproduktion der Druck-Ausgabe 30 October 2003
Gesehen am 27.11.2023
DOI funktioniert nicht / 27.11.2023